Konsekwencje nowego budownictwa mieszkaniowego dla porządkowania łódzkiej przestrzeni - Sikora, Dorota A. (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2005)
One of the main factors that affects the social and the spatial structure of the city are the housing resources. The influence of this resources for the city development covers also the spatial and economic aspects. The spatial management is the city officials task. Local government should have the long term policy of housing development. The lack of this policy can lead to chaos in town planning. Visible effects of this chaotic planning can be seen in the city of Łódź. (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1083, s. 364-371